Kompetensi Teknologi Informasi pada Perusahaan di Industri Jasa, Manufaktur dan Retail - Caroline, Angela; Kornarius, Yoke Pribadi; Gunawan, Agus (Universitas Pendidikan Indonesia, 2023)
The right use of technology can enhance the improvement of operational processes. However, the success rate of the use of this technology is inseparable from the competence of information technology. Therefore, the company should facilitate information technology competency improvement. A challenging question is whether the managers of service, manufacturing, and retail industry must focus on the same information technology competency, or they should focus on difference ones, considering the industry’s uniqueness. This study uses a survey method. The data obtained were 448 respondents and then processed using ANOVA and cross tabulation. The results showed that there were significant differences in those three components of information technology competency between manufacturing and retail-service. This is due to differences in market development strategy, such as companies needing new branches to reach new markets or companies labor intensive or not.